Acupuncture as a primary and independent treatment in the acute phases of sudden sensorineural hearing loss: Case Report. Issue 26 (June 2016) - Jin, Yuanyuan; Lu, Ming
Abstract : Abstract: Sudden sensorineural hearing loss (SSHL) is an otological emergency defined as a rapid hearing loss, seriously affects patient's social life. To data, no study has reported the treatment by acupuncture alone in the acute phase. In this report, Acupuncture and Moxibustion therapy of excitation-focus transfer is outlined. The patient was a 26-year-old young woman who had an SSHL coupled with ear fullness. The patient had no past medical history, but she had undergone variable emotions and had a history of excessive noise exposure. The patient refused to receive any medicine especially steroids and hyperbaric oxygen therapy. She just only received acupuncture treatment. Her symptoms and outcome measurements were improved every week and completely recovered after the last week. Even though the article presents a single case and is based on self-reports, there are very clear trends on how patients with SSHL responded to acupuncture treatments.